2015
DOI: 10.1002/nbm.3342
|View full text |Cite
|
Sign up to set email alerts
|

A study of the relationship of metabolic MR parameters to estrogen dependence in breast cancer xenografts

Abstract: 1H Magnetic Resonance Spectroscopy (MRS), 31P MRS and Diffusion Weighted MRI (DW-MRI) were applied to study the metabolic changes associated with estrogen dependence in estrogen receptor (ER) positive BT-474 and triple negative HCC1806 breast cancer xenografts supplemented with or without 17β-estradiol (E2) at a dose of 0.18 or 0.72 mg/pellet. Furthermore, the effect of estrogen withdrawal on metabolism of BT-474 and HCC1806 breast cancer xenografts were studied on day 0, day 2 and day 10. Increasing the dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These differences could be explained by lower mRNA expression of ChoK (α and β) and higher expression of PLA group 4A in basal tumor xenografts ( 61 ). In another experimental subcutaneous model expressing basaloid TNBC markers (HCC1806), phosphomonoesters (which include PCho) and lactate levels were modulated by tumor size ( 62 ).…”
Section: Ptdcho Metabolism In Tnbcmentioning
confidence: 99%
“…These differences could be explained by lower mRNA expression of ChoK (α and β) and higher expression of PLA group 4A in basal tumor xenografts ( 61 ). In another experimental subcutaneous model expressing basaloid TNBC markers (HCC1806), phosphomonoesters (which include PCho) and lactate levels were modulated by tumor size ( 62 ).…”
Section: Ptdcho Metabolism In Tnbcmentioning
confidence: 99%
“…4 , E2 along does not have much effect on cell proliferation after knockdown HER2, but this does not mean that the effect of tamoxifen is independent of ER in BT474 cells. Many previous studies have confirmed the reactivity of BT474 cells to estrogen [ 29 31 ]. In our study, the MTT assays were conducted in BT474 cells transfected with siRNA targeting HER2 24 h, and treated with 17β-E2 (10 nmol/L) and/or tamoxifen (TAM) (1 μmol/L) for another 48 h. BT474 is a cell that doubles for a long time.…”
Section: Discussionmentioning
confidence: 75%
“…Among the biochemical and molecular factors contributing to metabolic differences in BC subtypes, the expression of ER makes BC cells susceptible to estrogen-mediated effects on glucose and lactate metabolism [102]. In fact, the existence of a link between estrogen and lactate metabolism in BC cells has been well known for decades [103].…”
Section: Lactate In Bc Metabolism and Tumorigenesismentioning
confidence: 99%